Effects of cognitive interventions with video games on cognition in healthy elderly people: a systematic review - Graciela Akina Ishibashi; Gabriela dos Santos; Ana Paula Bagli Moreira; Cássia Elisa Rossetto Verga; Guilherme Alves da Silva; Tiago Nascimento Ordonez; Luiz Carlos de Moraes; Patrícia Prata Lessa; Sonia Maria Dozzi Brucki; Thais Bento Lima da Silva (Arquivos de Neuro-Psiquiatria)
Background Currently, studies using video games as an intervention to improve cognitive functions in the elderly are on the rise. Objective To investigate and evaluate the effects of cognitive interventions using video games on cognition in healthy elderly people published in the last ten years. Methods A systematic review involving a qualitative analysis carried out between July and September 2021on the SciELO, LILACS and MEDLINE databases.. Results A total of 262 articles were identified in the initial search. After exclusion of duplicates, analysis of titles/abstracts and of the full text, a final total of 9 studies were included in the review. The objectives of the studies included investigating the effects on cognition of cognitive training (CT) programs using video games compared to programs using entertainment games or to low-intensity CT games. Despite the growing number of studies, many of them were focused on cognitive rehabilitation in elderly people with some degree of cognitive impairment, and few involved training among healthy elderly people. Conclusion According to the studies analyzed, the interventions involving CT with video games promoted significant improvements in processing speed and working memory, but no improvements in executive functions.